Developing Teaching Skills in Doctoral Programs: The Current Status and Perceived Needs. - Edwards, James B.; Ingram, Robert W.; Sanders, Howard P. (The Accounting Review, 1981)
ABSTRACT: This research compares (1) current efforts to prepare doctoral candidates to be educators and (2) departmental administrators' perceptions of the need for educational training. One questionnaire was mailed to doctoral program directors of schools offering doctorates in accounting and another was mailed to department administrators of schools offering undergraduate and graduate degree programs in accounting. Analysis of the responses indicates that differences exist between the level of training in teaching currently provided in doctoral programs and the perceived need for such training by departmental administrators. Eighty-three percent of responding departmental administrators felt that teaching skills received inadequate attention in doctoral programs.